Iron and hepcidin mediate human colorectal cancer cell growth - Wannapa Sornjai (2020)
© 2020 Elsevier B.V. High dietary iron intake is a risk factor for the development of colorectal cancer. However, how iron subsequently impacts the proliferation of colorectal cancer cells remains unclear. This study determined the expression of six iron regulatory genes in twenty-one human colorectal cancer (CRC) biopsies and matched normal colonic tissue. The results show that only hepcidin and ferritin heavy chain expression were increased in CRC biopsies as compared to matched normal tissues. Four established human CRC cell lines, HT-29, HCT-116, SW-620 and SW-480 were subsequently examined for their growth in response to increasing concentrations of iron, and iron depletion. Real time cell growth assay showed a significant inhibitory effect of acute iron loading in HCT-116 cells (IC50 = 258.25 μM at 72 h), and no significant effects in other cell types. However, ten week treatment with iron significantly reduced HT-29 and SW-620 cell growth, whereas no effect was seen in HCT-116 and SW-480 cells. Intracellular labile iron depletion induced the complete growth arrest and detachment of all of the CRC cell types except for the SW-620 cell line which was not affected in its growth. Treatment of starved CRC cells with hepcidin, the major regulator of iron metabolism, induced a significant stimulation of HT-29 cell growth but did not affect the growth of the other cell types. Collectively these results show that iron is central to CRC cell growth in a manner that is not identical between acute and chronic loading, and that is specific to the CRC cell type.